PENGARUH PENGGUNAAN MEDIA ANIMASI DALAM PEMBELAJARAN IPS TERHADAP MOTIVASI BELAJAR SISWA KELAS IV SD NEGERI MANNURUKI - Alannasir, Wahyullah (Universitas Negeri Makassar, 2016)
The objective of study at manuruki elementari schole greade are (1) to now the student learning motivation in social study. (2) to she if the animation media usage in social study learning of class IV SD Negeri Mannuruki? (2) how the students motivation in learning IPS with the use of animation media Elementary School fourth grade students Mannuruki? (3) whether there is influence of media use animation in teaching social studies to students motivation Mannuruki Elementary School fourth grade?. This research uses experimental research (true experimental design. Data collection Â techniques used were: observation, interviews, and questionnaires. The analisis of the data use is deskriptif to describe to proces of learning by using animation media and the student motivation, and inferential analisis isÂ used to teks the risert hipotesis by using tetest. and Â The results showed that: (1) The use of animation media in teaching social studies have stages of learning in which, every meeting there are three main stages were carried out by teachers namely planning, implementation and evaluation are then designed in accordance with the steps for using media animation with both categories. (2) learning motivation of students in social study on student learning motivation, before and after learning by using animation media has increased significantly ie before the treatment is in the category enough and after treatment increased student motivation with very good category. (3) the use of the animation media influence the studensâ motivation to learn at the fourth grade of mannuruki elementary school.Â Â Â Â